2010
DOI: 10.1159/000320608
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implants in Forty-Eight Children with Cochlear and/or Vestibular Abnormality

Abstract: CT and MRI scans for 48 children with cochlear and/or vestibular abnormality were classified in decreasing severity; common cavity, Mondini plus enlarged vestibular aqueduct, Mondini dysplasia alone and enlarged vestibular aqueduct alone. No significant relationship between degree of cochlea abnormality and surgical issues (cerebrospinal fluid gusher, depth of insertion, number of electrodes) or speech perception/language outcomes was found. A significant relationship was observed between cerebrospinal fluid g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…[16][17][18][19][20] Various methods are reported to prevent facial nerve injury during cochlear implantation in patients with inner-ear anomalies. For cochleostomy, Sennaroglu and Saatci used a combined anteroposterior approach through the ear in which the facial nerve crossed over the oval and round windows.…”
Section: Figmentioning
confidence: 99%
“…[16][17][18][19][20] Various methods are reported to prevent facial nerve injury during cochlear implantation in patients with inner-ear anomalies. For cochleostomy, Sennaroglu and Saatci used a combined anteroposterior approach through the ear in which the facial nerve crossed over the oval and round windows.…”
Section: Figmentioning
confidence: 99%
“…For these reasons, malformation of the cochlea was considered a contra-indication to cochlear implant surgery in the early years of cochlear implantation in children, and it is still not possible to implant some of these children (Bamiou et al, 2001). Despite these difficulties, initial results for small numbers of children with cochlear anomalies have shown that implantation is possible, with some children achieving speech perception and language results similar to those without anatomical abnormalities (Chadha et al, 2009;Dettman et al, 2011). Children with a common cavity anomaly (a single cavity in the cochlea) and other more severe syndromic anomalies have achieved much poorer results (Bauer et al, 2002;Chadha et al, 2009;Lanson et al, 2007;Loundon et al, 2003;Young et al, 1995).…”
Section: Candidacy and Selected Aetiologies/pathologies Of Deafnessmentioning
confidence: 99%
“…Many papers have been published on the surgical outcomes of cochlear implantation performed in patients with CVM using these classification systems [Tucci et al, 1995;Luntz et al, 1997;Woolley et al, 1998;Ito et al, 1999;Eisenman et al, 2001;Papsin, 2005;Kim et al, 2006;Dettman et al, 2011;Adunka et al, 2012]. The systems allow the clinician to estimate what might happen during and after cochlear implantation surgery in patients with CVM and to communicate with other clinicians when discussing a patient with CVM.…”
Section: Introductionmentioning
confidence: 99%
“…The systems allow the clinician to estimate what might happen during and after cochlear implantation surgery in patients with CVM and to communicate with other clinicians when discussing a patient with CVM. There have been several comparative studies on postimplantation performance in a large number of CVM subjects and control subjects [Eisenman et al, 2001;Papsin, 2005;Kim et al, 2006;Dettman et al, 2011;Adunka et al, 2012]. Although the data were based on the findings of a few representative malformations such as incomplete partition, common cavity and enlarged vestibular aqueduct [Papsin, 2005;Dettman et al, 2011;Adunka et al, 2012] or were based on the mean value in children grouped arbitrarily, for example by grouping different types of malformation into one group (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation